Analysis of the molecular response of Pseudomonas putida KT2440 to the next-generation biofuel n-butanol - Simon, Oliver; Klebensberger, Janosch; Mükschel, Björn; Klaiber, Iris; Graf, Nadja; Altenbuchner, Josef; Huber, Armin; Hauer, Bernhard; Pfannstiel, Jens (Journal of proteomics, 2015)
To increase the efficiency of biocatalysts a thorough understanding of the molecular response of the biocatalyst to precursors, products and environmental conditions applied in bioconversions is essential. Here we performed a comprehensive proteome and phospholipid analysis to characterize the molecular response of the potential biocatalyst Pseudomonas putida KT2440 to the next-generation biofuel n-butanol. Using complementary quantitative proteomics approaches we were able to identify and quantify 1467 proteins, corresponding to 28% of the total KT2440 proteome. 256 proteins were altered in abundance in response to n-butanol. The proteome response entailed an increased abundance of enzymes involved in n-butanol degradation including quinoprotein alcohol dehydrogenases, aldehyde dehydrogenases and enzymes of fatty acid beta oxidation. From these results we were able to construct a pathway for the metabolism of n-butanol in P. putida. The initial oxidation of n-butanol is catalyzed by at least two quinoprotein ethanol dehydrogenases (PedE and PedH). Growth of mutants lacking PedE and PedH on n-butanol was significantly impaired, but not completely inhibited, suggesting that additional alcohol dehydrogenases can at least partially complement their function in KT2440. Furthermore, phospholipid profiling revealed a significantly increased abundance of lyso-phospholipids in response to n-butanol, indicating a rearrangement of the lipid bilayer. n-butanol is an important bulk chemical and a promising alternative to gasoline as a transportation fuel. Due to environmental concerns as well as increasing energy prices there is a growing interest in sustainable and cost-effective biotechnological production processes for the production of bulk chemicals and transportation fuels from renewable resources. n-butanol fermentation is well established in Clostridiae, but the efficiency of n-butanol production is mainly limited by its toxicity. Therefore bacterial strains with higher intrinsic tolerance to n-butanol have to be selected as hosts for n-butanol production. Pseudomonas bacteria are metabolically very versatile and exhibit a high intrinsic tolerance to organic solvents making them suitable candidates for bioconversion processes. A prerequisite for a potential production of n-butanol in Pseudomonas bacteria is a thorough understanding of the molecular adaption processes caused by n-butanol and the identification of enzymes involved in n-butanol metabolization. This work describes the impact of n-butanol on the proteome and the phospholipid composition of the reference strain P. putida KT2440. The high proteome coverage of our proteomics survey allowed us to reconstruct the degradation pathway of n-butanol and to monitor the changes in the energy metabolism of KT2440 induced by n-butanol. Key enzymes involved in n-butanol degradation identified in study will be interesting targets for optimization of n-butanol production in Pseudomonads. The present work and the identification of key enzymes involved in butanol metabolism may serve as a fundament to develop new or improve existing strategies for the biotechnological production of the next-generation biofuel n-butanol in Pseudomonads. [Display omitted] •Response of Pseudomonas putida KT2440 to n-butanol was analyzed by 2-D DIGE and LC–MS/MS.•n-butanol degradation pathway in P. putida KT2440 was elucidated.•Proteomics results were confirmed by analysis of deletion mutants of key enzymes.•New targets for improved biotechnological production of n-butanol were identified.•Changes of the phospholipid profile induced by n-butanol were analyzed.